PENERAPAN MODEL KOOPERATIF TIPE SOMATIC AUDITORY VISUAL INTELLECTUAL TERHADAP TINGKAT KEMAMPUAN BERPIKIR FORMAL SISWA PADA PEMBELAJARAN FISIKA KELAS X SMA N 1 KUBU ROKAN HILIR - Elvi Khairunnisa; M.Nor M.Nor; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine the influence of cooperative model somatic auditory visual intellectual type toward the level of students’ formal thinking ability on physics learning at x class of SMA N 1 Kubu Rokan Hilir. The type of this study was quasi experiment with intact group comparison design. The population in this study consisted of 3 classes. 2 classes was chosen as the sample of study based on normality and homogeneity test. They were acted as experiment and control classes the data collection was done by giving formal thinking ability test. The data was analyze by descriptive and inferential analysis. The result showed that there was a significant difference toward students’ formal thinking ability between class experiment which was used cooperative model somatic auditory visual intellectual type and control class which used convention learning. Students’ formal thonking ability at the experimental class was higher than the control class. It can be concludet that the cooperative model somatic auditory visual intellectual type has a positive influence toward students’ formal thinking ability.Key Words: Cooperative Model Somatic Auditory Visual Intellectual, Formal Thinking Ability,Temperature And Heat